Beneficial effects of bempedoic acid treatment in polycystic kidney disease cells and mice - Hallows, Kenneth R.; Li, Hui; Saitta, Biagio; Sepehr, Saman; Huang, Polly; Pham, Jessica; Wang, Jonathan; Mancino, Valeria; Chung, Eun Ji; Pinkosky, Stephen L.; Pastor-Soler, Núria M. (Frontiers in Molecular Biosciences, 2022)
ADPKD has few therapeutic options. Tolvaptan slows disease but has side effects limiting its tolerability. Bempedoic acid (BA), an ATP citrate-lyase (ACLY) inhibitor FDA-approved for hypercholesterolemia, catalyzes a key step in fatty acid/sterol synthesis important for cell proliferation. BA is activated by very long-chain acyl-CoA synthetase (FATP2) expressed primarily in kidney and liver. BA also activates AMPK. We hypothesized that BA could be a novel ADPKD therapy by inhibiting cyst growth, proliferation, injury, and metabolic dysregulation via ACLY inhibition and AMPK activation. Pkd1-null kidney cell lines derived from mouse proximal tubule (PT) and collecting duct (IMCD) were grown in 2D or 3D Matrigel cultures and treated ± BA, ± SB-204990 (another ACLY inhibitor) or with Acly shRNA before cyst analysis, immunoblotting or mitochondrial assays using MitoSox and MitoTracker staining. Pkd1fl/fl;Pax8-rtTA;Tet-O-Cre C57BL/6J mice were induced with doxycycline injection on postnatal days 10 and 11 (P10-P11) and then treated ± BA (30 mg/kg/d) ± tolvaptan (30-100 mg/kg/d) by gavage from P12-21. Disease severity was determined by % total-kidney-weight-to-bodyweight (%TKW/BW) and BUN levels at euthanasia (P22). Kidney and liver homogenates were immunoblotted for expression of key biomarkers. ACLY expression and activity were upregulated in Pkd1-null PT and IMCD-derived cells vs. controls. Relative to controls, both BA and SB-204990 inhibited cystic growth in Pkd1-null kidney cells, as did Acly knockdown. BA inhibited mitochondrial superoxide production and promoted mitochondrial elongation, suggesting improved mitochondrial function. In ADPKD mice, BA reduced %TKW/BW and BUN to a similar extent as tolvaptan vs. untreated controls. Addition of BA to tolvaptan caused a further reduction in %TKW/BW and BUN vs. tolvaptan alone. BA generally reduced ACLY and stimulated AMPK activity in kidneys and livers vs. controls. BA also inhibited mTOR and ERK signaling and reduced kidney injury markers. In liver, BA treatment, both alone and together with tolvaptan, increased mitochondrial biogenesis while inhibiting apoptosis. We conclude that BA and ACLY inhibition inhibited cyst growth in vitro, and BA decreased ADPKD severity in vivo. Combining BA with tolvaptan further improved various ADPKD disease parameters. Repurposing BA may be a promising new ADPKD therapy, having beneficial effects alone and along with tolvaptan.